Design and Implementation Plan of Process and Team Based Organization in Information Technology Division in Bank Central Asia - Pramudita, Angga; Welly, John (The Indonesian Journal of Business Administration, 2015)
Abstract – Bank Central Asia is one of the biggest private bank in Indonesia and is known for the its most innovative information technology service. Future banking competition will definitely require information technology as the main element. Branchless banking, digital channel, mobile banking are all IT related banking service which will be the next trend. In todays business, competitive advantage and technology are easily imitated by the competitors, and change happens very frequent and fast. Bank Central Asia should invest in its organization capabilities instead of gaining competitive advantage in its business model and strategies to adapt the very fast changing business environment. In the future, innovation in IT banking services will not dominantly be totally new products but in the form of process or service innovation. With the high demand of process based IT projects, more demand from business units to deliver variative, parallel, and complex IT related projects, GSIT as the IT division in Bank Central Asia has to adapt itself with the upcoming business needs and business environment. To grow and adapt itself with the process innovation environment, GSIT as an organization has to place itself in the business process level mindset, not the functional or products based organization structure. To absorb abundant IT projects with specific requirements and characteristics and to be self directed with minimal intervention from managements, GSIT needs to adopt team based organization concept with balanced and proper team and job design. The holistic framework of process and team based organization is hoped to accommodate resources management in GSIT which is now growing into a massive IT organization. For the transformation to process and team based organization be successful and effective, strategic and sound implementation plan with short implementation duration and proper evaluation framework is designed along with skilled, competent, and experienced agent of changes such as senior IT managers, senior HCM managers, external OD consultants, business solution unit, and project management unit. The entire transformation process is covered by DICE framework and General Model Of Planned Change which are tools to guide and measure organization intervention process. Keywords: team based organization, process based organization, business process, project management, organization resources management, organization development, process innovation, process based IT projects